TEACHING READING BY USING SPOTLIGHT STRATEGY AT SENIOR HIGH SCHOOL - Niko, Bambang Putra; Yelfiza, Yelfiza (Pendidikan Bahasa Inggris, 2013)
Alhamdulillahirabbilâalamin, the writer praises to Allah SWT who has given the writer healthy, opportunity, knowledge, spirit, and patient to finish this paper. He also sends his greeting and shalawat to the prophet Muhammad SAW the âuswatunhasanaâ for Muslims.Â Â Â Â Â Â Â Â Â Â Â  On this occasion, Firstly, the writer would like to express his deepest gratitude to his advisor, Rusmala Dewi, S.Pd who has given her meaningful guidance, knowledge, corrections, suggestions, comments, great willingness, and time to support him in finishing his paper. Secondly, the writer also expresses gratitude to Dra. Yelfiza, M.Pd, the head of English Department and Afridelfi, S.Pd the secretary of English Department.Â Â Â Â Â Â Â Â Â Â Â  Finally, the writer would like to express his gratitude to his beloved mother, father, brother and sisters, all of big family who always give their love, support as material supported and psychological to finish his paper. Then, the writer would also give his thanks to his beloved friends who have motivated, support and always be together during finishing this paper.Â Â Â Â Â Â Â Â Â Â Â  The writer realizes that this paper far from being perfect and he welcomes any comments and suggestions to make this thesis be perfect. The writer hopes that this paper will useful and helpful for him and anybody those who are interested in writing paper.